Jual Beli Suara dalam Pemilu Perspektif Hukum Islam - Muhammad Fadil Zuhri; Siti Arawiyyah Ardi; Maysa Putri Hairana Lubis; Aditya Dwipa Alkanzu; MHD. Sodikin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The practice of vote-buying and money politics in elections is a common issue found in the democratic process, which contradicts the principles of Islamic law. Offering money or basic necessities to the public with the intention of influencing votes is considered bribery. Transactions between legislative candidates and voters in exchange for certain rewards raise serious ethical and legal concerns from an Islamic perspective. In Islamic law, transactions that involve uncertainty (gharar), manipulation, and dishonesty are not permissible because they go against the principles of justice, transparency, and integrity outlined in Sharia. Vote-buying is regarded as an act that corrupts trust (amanah), as candidates involved fail to fulfill the rights and trust granted by the voters. This practice also creates social injustice, as it can unfairly affect election results and harm the interests of the broader society. Therefore, from the perspective of Islamic law, vote-buying is not only considered haram but also violates the fundamental principles of muamalah, which demand fairness and honesty in every transaction.